Breaching boundaries: reflections on the journey towards a transdisciplinary arts and sciences undergraduate degree programme to address global challenges. - Richards, Mary E.; Hussein, Mandekh; Castro-Sánchez, Enrique; Martin, Olwenn (Humanities & Social Sciences Communications, 2024)
This commentary reflects upon the progress, limitations, and some of the pitfalls of one UK London-based HE institution's development of a trans-disciplinary arts and sciences undergraduate degree programme specifically designed to build knowledge and confidence in students to both reflect upon and effectively respond in constructive and just ways to some of the 'global challenges' facing society. It does not challenge the importance and necessity of specialist expertise but sees the potential of a trans-disciplinary approach to education as not just complementary but increasingly valuable to a wider range of graduates. Graduates needed to lead systems change and facilitate wider appreciation and practical understanding of multidimensional problem-solving, the importance of stakeholder engagement and more holistic systems thinking, something that should not be limited to those who have the opportunity and means to study Masters or PhD degrees. As one of a few UK universities that offer inter-disciplinary or trans-disciplinary undergraduate degrees and with some added insights from a former colleague who now works on University College London's (UCL) interdisciplinary BASc, we offer the following suggestions and advice for those interested in working towards developing trans-disciplinary provision. This includes the development of a financial model that allows students and staff to work between departments or faculties; an administrative structure that promotes communication and information sharing between different departments without compromising the requirements of data protection; the buy-in and support of senior leaders who both understand and can advocate for the benefits of a trans-disciplinary approach and explicit university-wide recognition of the staff who work on such programmes in terms of career progression and support for the trans-disciplinary research they undertake.